2020
DOI: 10.5812/gct.99206
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cervical Cancer Cell Line Hela by Human Wharton’s Jelly Stem Cells Through Induction of Apoptosis

Abstract: Background: Cervical cancer is one of the most common cancers of women in the world, which causes high mortality. The human umbilical cord Wharton's jelly stem cells (hWJSCs) can inhibit various cancer cells. Objectives: This study aimed to investigate the effects of conditioned medium and cellular extract of human umbilical cord hWJSCs on cervical cancer cell line, Hela. Methods: After isolation and primary culture of hWJSCs, conditioned medium and cellular extracts of hWJSCs were prepared, and its anti-proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In this regards, our study demonstrated that the hWJSC-CM and hWJSC-CL signi cantly upregulated mRNA expression of BAX and SMAC genes (as pro-apoptotic genes) as well as downregulated mRNA expression BCL2 and SURVIVIN genes (as anti-apoptotic protein) in GC cells. In a study by Ghorbani and Maleki reported that the hWJSCs induces apoptosis through upregulation and down-regulation of BAX and BCL2 genes expression, respectively [24]. In another study by Elias et al reported that the hWJSCs up-regulated and down-regulated mRNA expression of P53 and BCL2 genes that leads to induction of apoptosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…In this regards, our study demonstrated that the hWJSC-CM and hWJSC-CL signi cantly upregulated mRNA expression of BAX and SMAC genes (as pro-apoptotic genes) as well as downregulated mRNA expression BCL2 and SURVIVIN genes (as anti-apoptotic protein) in GC cells. In a study by Ghorbani and Maleki reported that the hWJSCs induces apoptosis through upregulation and down-regulation of BAX and BCL2 genes expression, respectively [24]. In another study by Elias et al reported that the hWJSCs up-regulated and down-regulated mRNA expression of P53 and BCL2 genes that leads to induction of apoptosis [20].…”
Section: Discussionmentioning
confidence: 99%